Violation of The Code of Journalistic Ethics in The News Tribunnews.com June 2022 - February 2023 Issue - Ika Nurhidayah; M. Achwan Baharuddin (Jurnal Ilmu Komunikasi PROGRESSIO, 2023)
The journalistic code of ethics is at the heart of a very fundamental press. A code of ethics is a delegated moral rule whose power depends on the practitioner. Its existence is nothing but a moral rule that is forbidden to break for any professional. The code of ethics exists as signs that should not be violated. As mentioned in press Law No. Article 0/1999 7 Paragraph 2 reads: journalists have and follow a journalistic code of ethics.” But in fact, the code of ethics, which is a signpost for journalists, is still vulnerable to being violated. Along with the development of the speed of information propagation, container media and news publishing have also experienced significant development. Among them began to present news publishing portals such as the web and social media. As for this study, researchers will examine one of the news portals in the form of websites, namely Tribunnews.com. in this study the researchers used content analysis method with qualitative approach. Based on the analysis process carried out on the contents of some news on the website Tribunnews.com issue June 2022-February 2023 researchers found 10 News that did not meet the qualifications of news in accordance with the Journalistic Code of ethics.